Energy content of soybean meal, importation of soy products, and viral detection in inoculated feed and feed ingredients - Blomme, Allison Kate (Kansas State University, 2022)
A series of experiments were conducted to evaluate the energy content of soybean meal, understand the trends of soy products being imported to the United States, and demonstrate infectivity and detection of swine viruses in swine feed and feed ingredients. For Exp. 1, 5 treatments consisting of a control diet with solvent-extracted soybean meal (SSBM) or four diets with gradually increasing (25, 50, 75, or 100%) replacement of SSBM with extruded, expelled soybean meal (MSBM) to determine the energy content of MSBM by caloric efficiency. Diets were mixed and feed to nursery pigs for 28 days. No evidence for differences (P > 0.05) were observed for ADG or ADFI, but increasing MSBM in the diet improved G:F and caloric efficiency of pigs (linear, P < 0.001). Using caloric efficiency to estimate NE of the MSBM relative to SSBM, MSBM was estimated to have a value of 2,566 kcal/kg. In conclusion, MSBM contains approximately 123% of the energy of SSBM, which improved feed efficiency when fed to nursery pigs. Experiment 2 evaluated soy imports into the US as a whole and from foreign animal disease positive (FAD-positive) countries to determine which products are being imported in the highest quantities and to observe potential trends in imports from FAD-positive countries. Twenty-one different Harmonized Tariff Schedule (HTS) codes from the US International Trade Commission database were queried and summarized to determine quantities (metric tonnes, MT) and breakdown of different soy product types being imported into the US from 2015 to 2020. Top exporters of soy products to the US from FAD-positive countries in 2019 and 2020 were India, Argentina, and Ukraine. The risk of FAD introduction to the US through soy imports can fluctuate based on where FAD outbreaks are occurring, shipping methods, and end usage of products. A system to monitor these factors could help make future decisions about trade and risk of FAD introduction to US swine herds. Experiment 3 aimed to develop a benchtop viral isolation assay for porcine reproductive and respiratory syndrome virus (PRRSV) in feed and feed ingredients. Four matrix types (soybean meal, dried distiller’s grains with solubles [DDGS], complete swine diet, or cell culture media) were inoculated with (PRRSV) and incubated at three temperatures (4°C, 23°C, or 37°C) with samples being processed at 1, 24, 48, and 72 hours post-inoculation (hpi). Each sample was used for viral isolation to determine infectivity and also analyzed via quantitative real time reverse transcriptase polymerase chain reaction (qRT-PCR) to measure PRRSV RNA in the sample. An interaction (P = 0.0278) was observed for matrix × temperature × hour for live virus detected in the model, with increasing temperature and DDGS causing PRRSV to be least infectious over time. Only matrix type influenced the quantity of viral RNA detected using qRT-PCR (P = 0.0319). The viral control had more viral RNA detected than DDGS with soybean meal and the swine diet being intermediate. This VI model demonstrates the ability of feed and individual feed ingredients to harbor infectious virus, and storage time and temperature influence virus inactivation. Experiment 4 aimed to evaluate 1) the effect of benzoic acid (BA) and an essential oil blend (EO) on PPRSV, porcine epidemic diarrhea virus (PEDV), and Senecavirus A (SVA) inoculated in feed and 2) the effect of EO on PEDV inoculated into a swine vitamin premix. For the first objective, four chemical treatments four treatments consisting of 0.5% BA, 0.5% BA and 200 ppm EO, 0.3% BA and 120 ppm EO, and 0.25% BA and 100 ppm EO were used in the complete feed to test the effect on detection of PRRSV, PEDV, and SVA via qRT-PCR. For the second objective, a vitamin premix with 2.68% EO and the same premix with 2.68% limestone were tested to determine the effects on PEDV RNA detection. The inoculated feed or premix was stored for 2, 5, and 15 d post-inoculation (dpi). In the first study, PEDV and SVA had a treatment × day interaction (P ≤ 0.008), with an effect of time on detection of PRRSV (quadratic, P = 0.038). In the second experiment, the use of the EO in the premix did not demonstrate a treatment × day interaction (P = 0.962), an effect of treatment (P = 0.066), or degradation over time (P > 0.279). The use of a BA and/or EO mitigant in this model did not provide evidence for viral mitigation through the addition of these feed additives in either feed or premix, but viral load was reduced in the feed matrix over time.
Keywords: Soy imports; Estimated net energy; Viral survival; Porcine reproductive and respiratory syndrome virus; Soybean meal; Feed safety